A narrative review of the knowledge, attitudes, and practices of healthcare professionals toward diabetic retinopathy - Khisimusi Debree Maluleke; Khisimusi Debree Maluleke; Saajida Mahomed (Frontiers in Medicine)
BackgroundDiabetic retinopathy (DR) is a leading cause of preventable vision loss worldwide. Early screening and diagnosis are critical in mitigating vision loss in patients with diabetes. This review aims to analyze existing research on healthcare professionals’ (HCPs) knowledge, attitudes, and practices regarding DR screening.MethodsA literature search was performed using four electronic databases: Medline, Google Scholar, Science Direct, and EBSCOhost. The search terms included synonyms connected by the Boolean operator “OR.” This search covered quantitative, qualitative, and mixed-methods research studies. The appraisal was done using the Joanna Briggs Institute’s critical tool. A total of 59 published articles were analyzed.ResultsForty-seven articles (79.7%) assessed knowledge of HCPs, 30 (50.8%) assessed attitudes, and 42 (71.2%) assessed practices related to DR screening and referrals. The studies reveal significant differences in knowledge, attitudes, and practices regarding DR among various HCPs. There was variation in levels of knowledge amongst various categories of HCPs, with nine studies reporting 100% knowledge of DR. Positive attitudes ranged from 13 to 100%. Similar variations were reported regarding practices, with many HCPs not screening patients for DR. Inadequate training, lack of screening resources like an ophthalmoscope, dilating eye drops, and being inundated with other responsibilities were common reasons for the gaps in knowledge and practices.ConclusionNon-ophthalmic HCPs’ knowledge, attitudes, and practices (KAP) regarding DR screening were unsatisfactory. The HCPs with an ophthalmic background had varying levels of KAP regarding DR, with some having good knowledge and others having deficiencies in applying screening guidelines and providing patient education. Regular in-service training is needed, particularly for non-ophthalmic HCPs, and resources should be available for screening at the primary care level.